Determinan Financial Distress Pada Perusahaan Bumn Di Bursa Efek Indonesia - Wahyuni, Titi Putri Nuji; Risal; Febriati; Renny Wulandari (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This study is a quantitative research that aims to determine the influence of liquidity, profitability, leverage, and sales growth on financial disclosure in state-owned companies on the Indonesia Stock Exchange for the period 2018-2022. Financial distress is a condition of a company where its finances are experiencing an unhealthy state or crisis, the measurement of financial distress uses the Altman Z-Score model, the population in this study is state-owned companies listed on the Indonesia Stock Exchange (IDX), with a sample of 10 State-Owned Enterprises (SOE) obtained by the purposive sampling method. The processing and testing technique uses multiple linear regression tests. The results of the study show that sales growth has no effect on financial distress. Meanwhile, liquidity has a significant negative effect, profitability has a significant positive effect and leverage has a significant negative effect on financial distress.